Ameliorating Endothelial Mitochondrial Dysfunction Restores Coronary Function via Transient Receptor Potential Vanilloid 1–Mediated Protein Kinase A/Uncoupling Protein 2 Pathway. Issue 2 (February 2016) - Xiong, Shiqiang; Wang, Peijian; Ma, Liqun; Gao, Peng; Gong, Liuping; Li, Li; Li, Qiang; Sun, Fang; Zhou, Xunmei; He, Hongbo; Chen, Jing; Yan, Zhencheng; et al.
Abstract : Coronary heart disease arising from atherosclerosis is a leading cause of cardiogenic death worldwide. Mitochondria are the principal source of reactive oxygen species (ROS), and defective oxidative phosphorylation by the mitochondrial respiratory chain contributes to ROS generation. Uncoupling protein 2 (UCP2), an adaptive antioxidant defense factor, protects against mitochondrial ROS-induced endothelial dysfunction in atherosclerosis. The activation of transient receptor potential vanilloid 1 (TRPV1) attenuates vascular dysfunction. Therefore, whether TRPV1 activation antagonizes coronary lesions by alleviating endothelial mitochondrial dysfunction and enhancing the activity of the protein kinase A/UCP2 pathway warrants examination. ApoE −/−, ApoE −/− /TRPV1 −/−, and ApoE −/− /UCP2 −/− mice were fed standard chow, a high-fat diet (HFD), or the HFD plus 0.01% capsaicin. HFD intake profoundly impaired coronary vasodilatation and myocardial perfusion and shortened the survival duration of ApoE −/− mice. TRPV1 or UCP2 deficiency exacerbated HFD-induced coronary dysfunction and was associated with increased ROS generation and reduced nitric oxide production in the endothelium. The activation of TRPV1 by capsaicin upregulated UCP2 expression via protein kinase A phosphorylation, thereby alleviating endothelial mitochondrial dysfunction and inhibiting mitochondrial ROS generation. In vivo, dietary capsaicin supplementation enhanced coronary relaxation and prolonged the survival duration of HFD-fed ApoE −/− mice. These effects were not observed in ApoE −/− mice lacking the TRPV1 or UCP2 gene. The upregulation of protein kinase A /UCP2 via TRPV1 activation ameliorates coronary dysfunction and prolongs the lifespan of atherosclerotic mice by ameliorating endothelial mitochondrial dysfunction. Dietary capsaicin supplementation may represent a promising intervention for the primary prevention of coronary heart disease. Abstract : Supplemental Digital Content is available in the text.